Before the Waiting Room (Short Documentary) - Christidis, Yiannis (My University, 2026)
Gabriel is an asylum seeker who lives in Cyprus, waiting for the Asylum Services to call him for an interview, and doesn't know if he will ever be called. Having fled Gambia, his story before his arrival is what puts an additional obstacle to his everyday life in uncertainty.